Current clinician perspective on non-vitamin K antagonist oral anticoagulant use in challenging clinical cases - Uğur Önsel Türk; Rezzan Deniz Acar; Taylan Akgün; Volkan Emren; Selçuk Kanat; Emir Karacağlar; Alper Kepez; Şeref Kul; Erdem Özel; Evrim Şimşek; Selcen Yakar Tülüce; Kamil Tülüce; et al. (KARE Publishing, 2020)
Objective: The evolution of non-vitamin K antagonist anticoagulants (NOACs) has changed the horizon of stroke prevention in atrial fibrillation (SPAF). All 4 NOACs have been tested against dose-adjusted warfarin in well-designed, pivotal, phase III, randomized, controlled trials (RCTs) and were approved by regulatory authorities for an SPAF indication. However, as traditional RCTs, these trials have important weaknesses, largely related to their complex structure and patient participation, which was limited by strict inclusion and extensive exclusion criteria. In the real world, however, clinicians are often faced with complex, multimorbid patients who are underrepresented in these RCTs. This article is based on a meeting report authored by 12 scientists studying atrial fibrillation (AF) in diverse ways who discussed the management of challenging AF cases that are underrepresented in pivotal NOAC trials. Methods: An advisory board panel was convened to confer on management strategies for challenging AF cases. The article is derived from a summary of case presentations and the collaborative discussions at the meeting. Conclusion: This expert consensus of cardiologists aimed to define management strategies for challenging cases with patients who underrepresented in pivotal trials using case examples from their routine practice. Although strong evidence is lacking, exploratory subgroup analysis of phase III pivotal trials partially informs the management of these patients. Clinical trials with higher external validity are needed to clarify areas of uncertainty. The lack of clear evidence about complex AF cases has pushed clinicians to manage patients based on clinical experience, including rare situations of off-label prescriptions.